Effective Tracking of Nationally Determined Contributions - Ross, Katherine (Department of Mechanical Engineering, 2021)
Under the Paris Agreement, all Parties are required to track and report progress toward the implementation and achievement of their nationally determined contributions (NDCs). This is an international obligation, so this thesis focuses on how NDC tracking can be useful from a domestic standpoint too. Accordingly, the central research question is: “how can tracking progress toward mitigation targets in NDCs be most effective?” The research question is investigated and answered through a case study on South Africa as one key method. Part of the case study develops a framework for effective NDC tracking—in essence, a structure for ensuring that NDC tracking is performance-oriented and supports the achievement of set objectives. The framework shows that NDC tracking is effective when it begins with planning (i.e. identifying the vision and objectives of NDC tracking), before establishing a means for achieving that vision through a logical framework approach—all set within the context of an enabling environment. There is regular feedback to support continual learning and improvement. NDC tracking is also effective when it furthers national priorities, improves policy performance, enhances understanding and transparency, promotes trust and accountability, and links climate action with socio-economic outcomes. The framework is applied to NDC tracking in South Africa, helping to illustrate the answer to the overall research question of the thesis by asking: “how effective is NDC tracking in South Africa?” Content analysis of key documents and in-depth interviews with key stakeholders reveal that South Africa is wellequipped for NDC tracking in certain areas but can improve in others. The thesis concludes with recommendations based on the analysis. Additionally, the application of the framework to six other developing countries through comparative analysis reveals that the NDC tracking framework is broadly applicable and not country specific. The framework developed in this thesis complements the international NDC tracking rules agreed to in 2018, by providing a possible approach for designing effective NDC tracking processes or evaluating the extent to which countries are prepared for NDC tracking and identifying areas for enhancement. While the framework is constrained to NDC mitigation tracking, it could be feasibly extended in future to encompass NDC adaptation tracking, or an even broader application for tracking all domestic climate change action.